Isoprenoids and protein prenylation: implications in the pathogenesis and therapeutic intervention of Alzheimer's disease. (4th May 2018) - Jeong, Angela; Suazo, Kiall Francis; Wood, W. Gibson; Distefano, Mark D.; Li, Ling
Abstract: The mevalonate–isoprenoid–cholesterol biosynthesis pathway plays a key role in human health and disease. The importance of this pathway is underscored by the discovery that two major isoprenoids, farnesyl and geranylgeranyl pyrophosphate, are required to modify an array of proteins through a process known as protein prenylation, catalyzed by prenyltransferases. The lipophilic prenyl group facilitates the anchoring of proteins in cell membranes, mediating protein–protein interactions and signal transduction. Numerous essential intracellular proteins undergo prenylation, including most members of the small GTPase superfamily as well as heterotrimeric G proteins and nuclear lamins, and are involved in regulating a plethora of cellular processes and functions. Dysregulation of isoprenoids and protein prenylation is implicated in various disorders, including cardiovascular and cerebrovascular diseases, cancers, bone diseases, infectious diseases, progeria, and neurodegenerative diseases including Alzheimer's disease (AD). Therefore, isoprenoids and/or prenyltransferases have emerged as attractive targets for developing therapeutic agents. Here, we provide a general overview of isoprenoid synthesis, the process of protein prenylation and the complexity of prenylated proteins, and pharmacological agents that regulate isoprenoids and protein prenylation. Recent findings that connect isoprenoids/protein prenylation with AD are summarized and potential applications of new prenylomic technologies for uncovering the role of prenylated proteins in the pathogenesis of AD are discussed. Graphical Abstract: